2020
DOI: 10.17756/jocd.2020-034
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and Obesity as the Risk Factors for Leukemia in the Mediterranean Countries

Abstract: It is known, that in countries with high and medium incomes, the proportion of people with overweight and obesity started to increase in the second half of the 20 th century, as well as the incidence rate of Non-infectious Chronic Diseases (NCD). The study of risk factors for leukemia in the Mediterranean countries showed, that the incidence of leukemia for men was 2 times higher in countries with a higher Quality of Life (QOL); a higher percentage of men with overweight, obesity and hypercholesterolemia; a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Radkevich and Radkevich evaluated the effect of daily food consumption on the risk of cardiovascular disease, and found that men living in high-income countries had a 3.9-fold risk of HT than those living in low-income countries, and that the risk was 9.5 times higher for women. 34 The findings of our study support these results, and it can be said that the likelihood of HT in women living in rural areas increases when obesity is present.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Radkevich and Radkevich evaluated the effect of daily food consumption on the risk of cardiovascular disease, and found that men living in high-income countries had a 3.9-fold risk of HT than those living in low-income countries, and that the risk was 9.5 times higher for women. 34 The findings of our study support these results, and it can be said that the likelihood of HT in women living in rural areas increases when obesity is present.…”
Section: Discussionsupporting
confidence: 85%
“…The literature shows a positive relationship between HT and obesity, physical inactivity, stress, excessive salt intake, and bad dietary habits. 8,11,33,34 de Souza Filho et al found that the risk of HT increases with an increase in BMI. 33 In our study, we found that as the BMI value increases, the risk of HT increases approximately 1-fold.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that cardiovascular diseases depend on income and do not depend on geographic latitude [37]. And diabetes does not depend on income, but depends on geographic latitude [38].…”
Section: Discussionmentioning
confidence: 81%